Problemy epistemologiczne analizy podgrup randomizowanych badań klinicznych - Rzepiński, Tomasz (Filozofia Nauki, 2016)
Subgroup analysis is one of the methods used in contemporary methodology of medicine for assessing the effects of undertaken therapy. It is often claimed that researchers who use the method overestimate its epistemic value. The main purpose of this paper is to analyze the credibility of conclusions formulated on the basis of subgroup analysis. Its findings will help to better understand the epistemological limitations of this method as well as to clarify its function in clinical trials.